Penerimaan Teknologi: Pengaruh Persepsi Kebergunaan dan Persepsi Kemudahgunaan ke Atas Niat Bertingkah Laku Terhadap E-Dagang di Kalangan Pengurusan Atasan IKS di Sabah - Naul, Franky (2011)
This study aims to determine the acceptance of e-commerce among top management in Small and Medium Industries in Sabah from perspective behavioural intention to use e-commerce. E-commerce refers to the process of preparing, buying and selling information, products or services with the help of computer and telecommunications networks that use Internet technology for commercial purposes. The theory of this study was adapted from the Technology Acceptance Model (TAM) by inserting the two independent variables and one dependent variable. Independent variables include the perceived usefulness and perceived ease of use. While the dependent variable is the behavioural intention to use e-commerce. Data obtained using a questionnaire instrumen involving 550 respondents consisting of senior management Small and Medium Industries (SMIs) in Sabah. However, only 281 received questionnaires completed and taken into account for analysis. Response rates were 51.1% of respondents. Analysis is performed using a descriptive test, correlation, regression and multiple regressions. Descriptive test is to determine the frequency and percentage of respondents profiles. Correlation test was to determine the relationship between two independent variables. While multiple regressions used to test the effect of the two independent variables on the dependent variable. Results of the study showed 37.4 percent of respondents have behavioural intention to use e-commerce. In addition, the perceived ease of use has significant relationship with the perception of usefulness. Multiple regression test results indicate that perceived usefulness and perceived ease of use have positive effect on behavioural intention to use e-commerce. Results of the study findings, several discussions and recommendations were put forward in this project paper.